2018
DOI: 10.1002/ghg.1817
|View full text |Cite
|
Sign up to set email alerts
|

The coupled effect of salt precipitation and fines mobilization on CO2 injectivity in sandstone

Abstract: Appreciable CO2 injectivity is required to inject large volumes of CO2 through a minimum number of wells. In situ geochemical CO2‐brine‐rock reactions may dissolve sandstone rock minerals, and consequently release fine particles into the pore fluid. If the fine particles (‘fines’) are mobilized during CO2 injection, well injectivity could be severely impaired. The transport of fines under CO2 injection conditions involves the complex multiphase flow of dry supercritical CO2, saline formation brine, and fine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…120 Salt precipitation is another cause of fines-induced injectivity impairments through making the pores susceptible to fines entrapment by size exclusion capture in thin pore throats. 82,121,122 Mineral dissolution is also likely to increase the portion of dislodged fines in saline aquifers; however, there are some arguments on how it affects the wellbore injectivity. For instance, Pearce et al 113 showed that at lower pH condition of CO 2 -rich brines, the impacts of fines migration can be either negative or positive.…”
Section: Factors Affecting the Injectivity Of Comentioning
confidence: 99%
See 2 more Smart Citations
“…120 Salt precipitation is another cause of fines-induced injectivity impairments through making the pores susceptible to fines entrapment by size exclusion capture in thin pore throats. 82,121,122 Mineral dissolution is also likely to increase the portion of dislodged fines in saline aquifers; however, there are some arguments on how it affects the wellbore injectivity. For instance, Pearce et al 113 showed that at lower pH condition of CO 2 -rich brines, the impacts of fines migration can be either negative or positive.…”
Section: Factors Affecting the Injectivity Of Comentioning
confidence: 99%
“…Despite the seemingly simple process of salt formation, there exist conflicting results regarding the influences of drying-out on CO 2 injectivity. , While most research has revealed the drastic injectivity impairments caused by a porosity reduction of 2–15% and a permeability decline of 13–83%, ,,, some other research has shown that the increased relative permeability of CO 2 , due to water vaporization, compensates for the negative impacts of pore plugging. ,,, Bacci et al claimed that such disagreements mainly arise from the role of brine mobility, and a significant porosity change only occurs under sufficiently high brine mobility when the continuous recharge of the precipitation front increases the salt concentration.…”
Section: Factors Affecting the Injectivity Of Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…For a cylindrical core, radius Rand length L reconstructed into a bundle of parallel, noninteracting capillary tubes with varying radii (r1,r2,r3,rN), it can be shown that, the total number of capillary tubes in the core is given by (Fig. ): N=34ϕ()Rri¯2…”
Section: Modeling Workmentioning
confidence: 99%
“…. r N ), it can be shown that, the total number of capillary tubes in the core is given by 44 (Fig. 6):…”
Section: Heating Of Co 2 In the Reservoirmentioning
confidence: 99%